Urgensi Pendidikan Karakter Di Kalangan Mahasiswa Ditinjau Dari Filsafat Progresivisme Pada Sekolah Tinggi Teologi Di Indonesia: Urgensi Pendidikan Karakter Di Kalangan Mahasiswa Ditinjau Dari Filsafat Progresivisme Pada Sekolah Tinggi Teologi Di Indonesia - Jenesa, Angel Gabriela (MAWAR SARON: Jurnal Pendidikan Kristen dan Gereja, 2024)
Nowadays, as time goes by, children's moral values ​​are increasingly decreasing due to bad relationships, which results in children's moral values ​​becoming bad, for example, drugs, brawls, bullying, etc. Of course, this is a matter of concern for the future life of the nation. Character education is a very important education to be applied at any university. This is due to a decrease in a person's moral values ​​due to the bad associations he receives. To develop positive moral values ​​in students, hard work by educators/lecturers is needed, and this can be seen from the level of success of a mission, namely how much progress is achieved. Therefore, the philosophy of progressivism is needed in the development of educational methods which can certainly produce the goals that a university wants to achieve. In this research, researchers used qualitative methods and analyzed descriptively. Meanwhile, the aim of this research is to see how effective character education is implemented at a campus or university. With this character education, through a progressivism approach, it is hoped that it can help students improve their character in behaving properly.